TINJAUAN HUKUM PENGGUNAAN DRONE ANTARA KEAMANAN PUBLIK DAN PERLINDUNGAN PRIVASI INDIVIDU - Muhammad Rhicco; Ardison Asri (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The rapid development of drone technology has brought significant innovations in various sectors, including military, photography, delivery, and surveillance. Although it offers efficiency and the ability to access difficult areas, the massive use of drones raises legal challenges related to the conflict between public security and individual privacy rights. Drones can be an effective tool for security surveillance, but their ability to record without permission also threatens privacy, such as incidents of drones falling or being used for espionage. This makes it interesting to discuss how current laws and regulations in Indonesia regulate the use of drone technology related to aspects of public security and protection of individual privacy? and what are the mechanisms for supervision and law enforcement against violations of privacy and public security involving the use of drone technology in Indonesia?. This study uses a juridical-normative method with a literature approach to analyze existing laws and regulations. The results show that Permenhub PM 37/2020 implicitly touches on aspects of privacy, it is realized that privacy protection requires more specific regulations. Therefore, Law Number 1 of 2009 concerning Aviation and especially Law Number 1 of 2024 concerning the Second Amendment to the ITE Law (along with PP Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions). Supervision and law enforcement of drone use in Indonesia is a collaborative and multi-layered effort involving various government agencies, a strict licensing system.